The Effect of Spiritual Well-Being, Social Support, and Gratitude on Hardiness among Parents of Children with Special Needs - Lusiani, Eli; Amalia, Maya; Fanisya, Fanisya (LifeSciFi, 2026)
Parents of children with special needs face complex psychological stressors that can challenge their resilience and well-being. Understanding the factors that enhance parental psychological hardiness is crucial for designing effective support strategies. This study aimed to examine the simultaneous influence of spiritual well-being, social support, and gratitude on the hardiness of parents with special needs children. A cross-sectional quantitative design was employed, involving 120 parents of children with special needs. Data were collected using validated instruments to assess spiritual well-being, social support, gratitude, and hardiness, and analyzed through multiple linear regression. The results indicate that all three factors significantly contribute to parental hardiness, with gratitude emerging as the strongest predictor, followed by spiritual well-being and social support. These findings highlight that hardiness is shaped by the interaction of internal strengths, such as emotional regulation and meaning-making, and external resources, including social and community support. The study underscores the importance of holistic interventions that integrate gratitude practices, spiritual reflection, and the reinforcement of social support networks to strengthen psychological hardiness among parents caring for children with special needs.